Digital Financial Services, Trust in Fintech, and Perceived Security in Influencing User Satisfaction and Continued Usage Intention. A Case Study of Gopay By PT Dompet Anak Bangsa - Nisa Nurrela; Diah Utami; Sella Sakilla Maharani; Jerry Heikal (Dinasti International Journal of Education Management and Social Science, 2025)
This study examines the impact of Digital Financial Services (DFS), Trust in Fintech (TF), and Perceived Security (PS) on User Satisfaction (US) and Continued Usage Intention (CUI) among GOPAY users, a fintech platform operated by PT Dompet Anak Bangsa. Utilizing Structural Equation Modeling with Partial Least Squares (SEM-PLS), data from 322 GOPAY users in Jabodetabek were analyzed to evaluate the relationships between variables. Findings reveal that DFS and PS significantly influence US (β = 0.541, p = 0.000; β = 0.437, p = 0.001), while TF shows no significant effect (β = 0.018, p = 0.916). US significantly mediates the effect on CUI (β = 0.553, p = 0.000). Directly, PS impacts CUI (β = 0.395, p = 0.000), whereas DFS and TF do not (β = -0.116, p = 0.062; β = 0.131, p = 0.230). DFS indirectly affects CUI through US with a total effect of 0.183. These results highlight US as a key mediator in driving CUI, with DFS and PS as critical factors. PT Dompet Anak Bangsa is recommended to enhance service quality, strengthen security systems, and prioritize user satisfaction as a strategic measure to foster user loyalty within the increasingly competitive fintech market.